2008
DOI: 10.1016/j.ijpharm.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a sodium-dependent vitamin C transporter (SVCT) in MDCK-MDR1 cells and mechanism of ascorbate uptake

Abstract: The objective of this research was to functionally characterize sodium-dependent vitamin C transporter (SVCT) in MDCK-MDR1 cells and to study the effect of substituted benzene derivatives on the intracellular accumulation of ascorbic acid (AA). Mechanism of AA uptake and transport was delineated. Uptake of [(14)C]ascorbic acid ([(14)C]AA) was studied in the absence and presence of excess unlabelled AA, anion transporter inhibitors, and a series of mono- and di-substituted benzenes. Transepithelial transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
4
34
0
1
Order By: Relevance
“…The presence of SVCT on corneal cells and Madin-Darby canine kidney cells has been previously reported from our laboratory (Luo et al, 2008; Talluri et al, 2006). Also, SVCT expression was shown on breast cancer epithelial cells (MDA-MB231 and T47D cells).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The presence of SVCT on corneal cells and Madin-Darby canine kidney cells has been previously reported from our laboratory (Luo et al, 2008; Talluri et al, 2006). Also, SVCT expression was shown on breast cancer epithelial cells (MDA-MB231 and T47D cells).…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, AA is usually obtained from exogenous sources through the dietary intake (Luo et al, 2008). AA uptake via specific transport system has already been reported in intestine (Maulen et al, 2003), brain (Castro et al, 2001), kidney (Bowers-Komro and McCormick, 1991), skin (Padh and Aleo, 1987), eye (Garland, 1991; Talluri et al, 2006) and bone (Dixon et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the physiological pH conditions (pH 7.2), RB-A-Vc became negatively-charged and difficult to permeate the cell membrane without the aid of transporters. 28 To further conrm the RB-A-Vc was transported by SVCTs, we examined the specicity of RB-A-Vc against SVCTs by Western blot assay. The results indicate there is only SVCT2 identied at $50 kDa, but no SVCT1 (at 65 kDa) was found in HEK-293T cells (Fig.…”
Section: Fluorescence Imaging Of Svcts In the Xed Cellsmentioning
confidence: 99%
“…There are some literature reports on the substrate specificity of the AsA transporter using biological tissues or cells. [28][29][30][31][32] As most AsA exists as a monovalent anion at physiological pH and SVCT has a high affinity for the ionic form, it has been suggested that the ionic interactions between SVCT and its substrates are the predominant driving forces for the binding of SVCT. 31,32) Studies by Rumsey et al 33) demonstrated that one of the structural requisites of AsA and its analogs for transport in cells is an S-absolute configuration at the C-4 position in a five-membered reduced ring with no substitution on the C-2 and C-3 positions, and that 6-deoxy-6-halogeno-Lascorbic acid is an effective compound for inhibiting AsA uptake.…”
Section: Resultsmentioning
confidence: 99%